2006
DOI: 10.1145/1132973.1132975
|View full text |Cite
|
Sign up to set email alerts
|

Constructing memory-minimizing schedules for multifrontal methods

Abstract: We are interested in the memory usage of multifrontal methods. Starting from the algorithms introduced by Liu, we propose new schedules to allocate and process tasks that improve memory usage. This generalizes two existing factorization and memory-allocation schedules by allowing a more flexible task allocation together with a specific tree traversal. We present optimal algorithms for this new class of schedules, and demonstrate experimentally their benefit for some real-world matrices from sparse matrix colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Liu [136] minimises the size of the active memory by rearranging the children of each node (hence creating an equivalent ordering) in order to minimise the peak active memory for processing the whole tree. In a series of papers, Agullo et al [2,3] and Guermouche and L'Excellent [102] elaborate on the issues addressed by Liu [136]. In these papers, algorithmic models that separate the concerns of I/O volume and the peak memory size are developed, and a new reorganisation of the computations within the context of an out-of-core multifrontal method are presented.…”
Section: Elimination Tree and The Multifrontal Methodsmentioning
confidence: 99%
“…Liu [136] minimises the size of the active memory by rearranging the children of each node (hence creating an equivalent ordering) in order to minimise the peak active memory for processing the whole tree. In a series of papers, Agullo et al [2,3] and Guermouche and L'Excellent [102] elaborate on the issues addressed by Liu [136]. In these papers, algorithmic models that separate the concerns of I/O volume and the peak memory size are developed, and a new reorganisation of the computations within the context of an out-of-core multifrontal method are presented.…”
Section: Elimination Tree and The Multifrontal Methodsmentioning
confidence: 99%
“…Finally, compute the resulting t i and take the split point to be the p i that gives the smallest t i . Guermouche and L'Excellent [2006] proved they obtain the optimal t i . Fig.…”
Section: The Assembly Order Of Child Nodesmentioning
confidence: 98%
“…However, numerical experiments have shown that this can also perform poorly because a chain of frontal matrices (at the active tree levels) must be stored. This led Guermouche and L'Excellent [2006] to propose computing, for each node, the optimal point at which to allocate the frontal matrix and start the assembly.…”
Section: The Assembly Order Of Child Nodesmentioning
confidence: 99%
See 2 more Smart Citations